Physicochemical, colour, textural, rheological and sensory properties of goat milk mozzarella cheeses as affected for acidulants: Goat milk mozzarella cheese with acidulants.. - Verma, Arun; Singh, Tarun Pal; V., Rajkumar; K., Gururaj; Singh, Manoj Kumar; Kushwah, Tanuja (Indian Journal of Dairy Science, 2023)
The present study aimed at investigating the effect of four acidulants, viz., acetic acid (CAA), citric acid (CCA), hydrochloric acid (CHA) and lactic acid (CLA) quality and acceptability of goat milk mozzarella cheese. No significant differences in the values of cheese yield, pH, protein and fat were observed among treatments. However, titratable acidity for CCA was significantly higher (p<0.05) than for other treatments. Moisture and ash contents in CAA were significantly higher (p<0.05) than in CLA and CHA. Cheese CAA had significantly lower (p<0.05) meltability than the other treatments. The fat leakage for treatment CCA was significantly higher (p<0.05) as compared to other cheeses. The Hunter colour redness (a*) value for CAA was significantly higher (p<0.05) compared to the other treatments. The yellowness (b*) value of treatment CAA was significantly higher (p<0.05) than the treatment CLA. The hardness and chewiness values for the treatments CAA and CHA were significantly higher (p<0.05) compared to the other two treatments. Cohesiveness and gumminess values were the highest for the treatment CAA, while lowest for the treatment CLA. The evaluation of frequency and temperature sweeps of cheese samples revealed that the storage modulus (G’) and loss modulus (G”) for the treatment CHA was the highest, while the treatment CLA had the lowest values. The sensory characteristics of the cheeses from different treatments were statistically similar except colour and appearance score, which was the highest for CCA. It can be concluded that though the type of acidulants had significant effects on various quality parameters of goat milk mozzarella cheese, their overall acceptability remained unaffected.